Military-Civil fusion and optimisation of urban industrial structure—an evidence from China - Zhaobin Sun; Xiwei Liu; Ling Li; Xiaoliang Yang (Cogent Economics & Finance, 2022)
China's military-civil fusion (MCF) policy has attracted global attention. Since 2010, China has constructed over 30 MCF national demonstration bases (MCFNDBs) to optimise local industrial structure and promote local economic development. However, the evaluation of the actual economic effects of these MCFNDBs has not reached a consensus. We use panel data for 285 cities from 2006-2017 to investigate the economic effect of MCFNDBs by difference-in-difference estimation. We find that constructing MCFNDBs are significantly beneficial to upgrading the urban industrial structure in less developed regions and provincial capital cities; however, it plays an insignificant role in the industrial structure rationalisation.
Keywords: C23; O14; R58; 330; military-civil fusion; industrial structure optimisation; industrial upgrading; industrial rationalisation; difference-in-difference